OUTCOME EFFECT DALAM PENGUKURAN KINERJA KEUANGAN DAN NONKEUANGAN : STUDI EKSPERIMEN - Wahyuningsih, Indah; Fitriyani, Dewi; Friyani, Rita (JAKK | Jurnal Akuntansi dan Keuangan Kontemporer, 2020)
This study aims to examine the outcome effect of decision making in assessing financial and non-financial performance. This study is an experimental research that involved 483 students. The research design was 2x4x2x2 between-subjects experimental design.. Hypothesis testing used univariate ANOVA. This research conclude: (1) there is significantly outcome effect in performance appraisal (2) there is no significantly result that non-financial measures extended outcome effect, and (3) there is no significantly result that controllability appraisal and outcome knowledge effect in minimizing outcome effect. This result also indicate when assessing financial performance will further enhance outcome effect